CTCF loss has limited effects on global genome architecture in Drosophila despite critical regulatory functions - Anjali Kaushal (Nature Portfolio, 2021)
Although the Drosophila genome has widespread contact domains and CTCF, it remains unclear whether CTCF-dependent domains exist in flies. Here, the authors ablate CTCF in Drosophila and find that CTCF is required to form a small fraction of all domain boundaries, suggesting differences in the role of CTCF for genome folding in flies and vertebrates.